Ethical Implications in the Use of Embryonic and Adult Neural Stem Cells - Rodrigo Ramos-Zúñiga; Oscar González-Pérez; Ana Macías-Ornelas; Vivian Capilla-González; Alfredo Quiñones-Hinojosa (Stem Cells International)
The advent and growth of technological advances have led to new routes of knowledge. Thereby, we currently face new challenges. We have just started to get a glimpse of the structural and functional role of neural stem cells in differentiation and migration processes, the origin of synaptic networks, and subsequent readjustments in specific circuits. A whole range of treatment possibilities originates from this knowledge that potentially can be used for different neurological diseases in humans. Although this is an encouraging scenario, it implies that the human brain is the object of such study, as well as its potential manipulation and transplantation. It is, therefore, pertinent that ethical principles should be followed in such research to have proper balance between what can be done and what should be done, according to every specific context. Hence, it is wise to consider ethical implications in every research project, along with potential clinical applications, under the principle of causing no harm, following risk and benefit rules in decision making and with respect of the human condition as a priority.